Rynek nawozów azotowych w Polsce – stan i kierunki zmian - Piwowar, Arkadiusz (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2012)
Growth of the agriculture potential is dependent on the scale of the use of industrial inputs, especially mineral fertilizers and chemical plant protection measures. Plants for proper growth, development and high-yielding need sufficient nutrients, containing mainly nitrogen. The aim of this article is to present the market of mineral nitrogen fertilizers in Poland, taking into consideration the range of products offered, the demand for nitrogenous fertilizers and changes in their prices. The study focuses on the period of time from 2004 until 2009.